Flora y vegetación de la cima del cerro Potosí, Nuevo León, México - García-Arevalo, Abel; Gonzalez-Elizondo, Socorro (Instituto de Ecología, A.C., 1991)
A study was made of the flora and vegetation of the summit of Cerro Potosí, located in the Southern part of the State of Nuevo León. The principal objective was to anafyze the changes that have occurred in the vegetation after 27 years, using as reference the paper of Beaman & Andresen (1966) on the vegetation and floristics of the area.Sampling by means of transects through four communities: alpine meadow, subalpine meadow, Pinus culminicola scrub and P. hartwegii forest was carried out. Intensive and selective collecting was accomplished above the altitudinal level of 3500 m.The results show that alpine meadow and P. culminicola scrub decreased their areas, and that P. culminicola is not resistant to fire. Some of the dominant elements of subalpine meadow increased their distribution. A vascular flora of 95 species in 77 genera and 36 families is reported. Protection of this fragüe and unique ecosystem is proposed.